Identification of Edible Mushroom Species in the City of Lodja and Its Surrounding (Sankuru Province) in Democratic Republic of Congo - Junior-Gauthier N. Wembodinga; Benoit O. Djanya; Irène Y. Ambale; Jean-Malabar D. Shokesole; Jean Bernard Z. Bosanza; Jean Paul Koto-Te-Nyiwa Ngbolua (Britain International for Academic Research (BIAR) Publisher, 2024)
The study was carried out in order to constitute a database necessary for the valorization of edible mushroom in the city of Lodja and it’s surrounding by the identification of the different species of mushrooms, the types of substrates on which grow as well as their natural habitats. The result obtained show that 20 species of edible mushrooms have been identified, 70% of which grow during the rainy season compared to 30% in the dry season. Concerning the habitat, 60% of mushrooms are harvested in forests, 25% are multipurpose and 15% are harvested on grassy formations. Regarding the specificity of substrates, 40% of species grow on land, 30% colonize dead palm trees, 15% use either dead palm tree and trees or dead wood, 10% grow on dead wood and only 4% evolve on plant detritus. In terms of abundance, 50% are abundant, 30% are less abundant and 20% are rare in the environment. Finally, 4 species (20%) namely: Ntelia amanitalosis, Lentinus tigrinus, Cantharellus rufopunetatus and Marasmius oreades, present potential for mushroom cultivation. Hence, the need to domesticate them in order to study their performance and diversify local production.